A historical and critical account of the teaching of English language and literature in English-medium universities in South Africa, with particular reference to the University of Cape Town and the South African College - Penrith, Mary Caroline (School of Education, 2015)
This thesis is an attempt to trace the development of the academic study of English Language and Literature in South Africa from its origins to 1971. It is a particular study of the South African College and the University of Cape Town, with reference, where necessary, to other centres. The influence of this institution on higher education in South Africa .and the amount of writing it has produced seem to justify such a selection.